The inhibition of the proton donor ability of bicarbonate promotes the electrochemical conversion of CO2 in bicarbonate solutions. Issue 48 (June 2021) - Gutiérrez-Sánchez, Oriol; Daems, Nick; Offermans, Willem; Birdja, Yuvraj Y.; Bulut, Metin; Pant, Deepak; Breugelmans, Tom
Graphical abstract: Highlights: Integrated CO2 capture and conversion via electrochemical conversion of bicarbonate proposed. The bicarbonate reduction mechanism involves a CO2 -mediated step, with CO2 being the substrate. Bicarbonate promote the hydrogen evolution reaction (HER), thus making the process inefficient. By using cationic surfactants, HER is inhibited while CO2 reduction (CO2 R) is promoted. A bicarbonate solution acts as a carbon pool enabling CO2 to be stored up to saturation levels (2.2 M). Abstract: Gaseous CO2 solutions are widely used for CO2 electrochemical conversion to various valuable products. However, capture, liberation and storage of gaseous CO2 prior to reduction is cumbersome and costly. CO2 electrocatalytic reduction from captured CO2 (in the form of concentrated bicarbonate solution) offers an option to optimize CO2 reduction processes. Using concentrated bicarbonate solutions from captured CO2 as large carbon feedstock and reducing CO2 directly from bicarbonate electrolyte remain a challenge. Indeed, current efficiency is too low (i.e. low selectivity and/or activity) as a consequence of the strong competition with the hydrogen evolution reaction, which bicarbonate promotes to a great extent. In this study, up to 2 M bicarbonate solution is used as electrolyte (mimicking a captured CO2 solution from an alkaline media) for a CO2 electrochemical reduction system, which potentially pretends to be a 2 M carbon source, compared to 0.033 M present in a saturated gaseous CO2 solution. In order to improve the Faradaic efficiency of the process and thereby making the CO2 electrocatalytic reduction from a bicarbonate feedstock an efficient system and attractive alternative for the reduction starting from gaseous CO2, a reaction mechanism where bicarbonate acts as a CO2 donor instead of as a proton donor is proposed. To achieve such property, we inhibit the proton donor ability of bicarbonate and water by covering the surface of the electrode with cationic surfactants, allowing non-polar molecules, like the CO2 derived from the equilibrium with bicarbonate, to diffuse to the surface of the electrode while avoiding bicarbonate and water to promote the hydrogen evolution reaction. To the best of our knowledge, the Faradaic Efficiency to formate obtained in this study (>70 %) sets a new benchmark in systems involving unsaturated and saturated bicarbonate solutions without previously purging CO2 .